2021
DOI: 10.5125/jkaoms.2021.47.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement in fresh extraction sockets

Abstract: Immediate implant placement (IIP) in fresh extraction sockets exhibits similar survival and success rates to delayed implant placement in healed sockets. Several advantages of IIP involve shortened total treatment time, reduction of the number of invasive surgeries, and subsequent reduction of patient discomfort due to lack of additional surgeries. The major shortcomings in IIP, however, include the inability to obtain early bony support, presence of a gap between the extraction socket and fixture, and the ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In this study, the aesthetic efect and satisfaction score of patients after implant surgery were further compared, and it was found that the aesthetic efect score and satisfaction score of patients in minimally invasive surgery group were higher than those in conventional surgery group. After minimally invasive implantation, the implanted root can be combined with the alveolar more closely, which is very compatible with human physiological functions, and has the same chewing function as human teeth [22]. Minimally invasive implant surgery can be designed according to the patient's face shape, the condition of the original teeth, etc., and fully consider the coordination of the patient's oral structure [23].…”
Section: Emergency Medicine Internationalmentioning
confidence: 99%
“…In this study, the aesthetic efect and satisfaction score of patients after implant surgery were further compared, and it was found that the aesthetic efect score and satisfaction score of patients in minimally invasive surgery group were higher than those in conventional surgery group. After minimally invasive implantation, the implanted root can be combined with the alveolar more closely, which is very compatible with human physiological functions, and has the same chewing function as human teeth [22]. Minimally invasive implant surgery can be designed according to the patient's face shape, the condition of the original teeth, etc., and fully consider the coordination of the patient's oral structure [23].…”
Section: Emergency Medicine Internationalmentioning
confidence: 99%
“…Any major trauma during the procedure; which causes failure in preservation of hard and soft tissue quality. 40 7. Occurrence of iatrogenic complications: such as sinus membrane perforation, buccal plate fracture, and so forth.…”
Section: Proposal Of a New Classification Systemmentioning
confidence: 99%
“…Evaluation of oral hygiene: poor oral hygiene may increase the failure and complications in IIP 5 Any major trauma during the procedure; which causes failure in preservation of hard and soft tissue quality 40 Occurrence of iatrogenic complications: such as sinus membrane perforation, buccal plate fracture, and so forth. Re‐evaluation of buccal bone thickness and bone quality.…”
Section: Proposal Of a New Classification Systemmentioning
confidence: 99%
“…In accordance with the established standards used to assess implant success and survival, the level of marginal bone changes during the early time mostly in the first year should be less than 1.5 mm [3][4]. Schulte with Heimke described immediate implants for the first time in 1976 [5][6]. Immediate implants placed in freshly extracted sockets are an alternative treatment instead of conventional dental implants for reducing physiologically resorbed alveolar ridge [7][8].…”
Section: Introductionmentioning
confidence: 99%